Intramolecular Hydrogen Bonding Involving Organic Fluorine: NMR Investigations Corroborated by DFT-Based Theoretical Calculations - Sandeep Kumar Mishra (Molecules, 2017)
The combined utility of many one and two dimensional NMR methodologies and DFT-based theoretical calculations have been exploited to detect the intramolecular hydrogen bond (HB) in number of different organic fluorine-containing derivatives of molecules, viz. benzanilides, hydrazides, imides, benzamides, and diphenyloxamides. The existence of two and three centered hydrogen bonds has been convincingly established in the investigated molecules. The NMR spectral parameters, viz., coupling mediated through hydrogen bond, one-bond NH scalar couplings, physical parameter dependent variation of chemical shifts of NH protons have paved the way for understanding the presence of hydrogen bond involving organic fluorine in all the investigated molecules. The experimental NMR findings are further corroborated by DFT-based theoretical calculations including NCI, QTAIM, MD simulations and NBO analysis. The monitoring of H/D exchange with NMR spectroscopy established the effect of intramolecular HB and the influence of electronegativity of various substituents on the chemical kinetics in the number of organic building blocks. The utility of DQ-SQ technique in determining the information about HB in various fluorine substituted molecules has been convincingly established.